Learning styles and academic performance: a correlational study among engineering university students - Cardenas Yauri, Maribel; Sánchez Ayte, Jorge Augusto; Vertiz Osores, Jacinto Joaquin; Valencia Reyes, Zanhy Leonor (Institute of Advanced Engineering and Science, 2025)
In a context of little explanation of the links between learning styles (LS) and academic performance (AP) in university students, a quantitative analysis of these relationships was proposed in mechanical and electrical engineering students from a public university in Lima, Peru. The Honey-Alonso learning styles questionnaire (CHAEA) was used to identify the students’ styles. Grades in various subjects were used as data on AP. Discriminant analysis and hierarchical clustering were applied to develop an explanatory model of the relationship. The findings revealed that most students were classified in a central level of AP. LS were distributed in order of relevance of contribution as: ‘theoretical’, ‘reflective’, ‘active’ and ‘pragmatic’. The ‘theoretical’ and ‘reflective’ styles showed greater affinity. Better clustering was observed in the ‘in process’ and ‘achievement’ levels of AP. The level of ‘starting’ was diffuse among students, preventing it from being clearly associated with any LS, although it is recommended not to dismiss it because it may represent students who require additional support from teaching staff. This research contributes a holistic view of the factors that influence university AP and highlights the importance of conducting further research in this field.